Multicriteria GIS-based assessment of biomass energy potentials in Nigeria - Ukoba, M. O.; Diemuodeke, E. O.; Briggs, T. A.; Ojapah, M. M.; Okedu, K. E.; Owebor, K.; Akhtar, K.; Ilhami, C. (Frontiers in Bioengineering and Biotechnology, 2024)
The geographical variability of biomass energy is an issue that requires the optima location of biomass energy facility. This research presents a multicriteria GIS-based assessment of biomass energy potentials and the appropriate siting of biomass plant in Nigeria. The study applies the weighted overlay multicriteria decision analysis method. Crop, and forest areas; settlement (energy supply areas); shrub/grass lands; barren land; waterbodies; distance from water sources; road accessibility; topography; and aspect are the criteria that were considered for locating the biomass facility in this study. The results suggest that the theoretical, technical and economical energy potentials of crop residues are highest in the north-east region of Nigeria and estimated at 1163.32, 399.73 and 110.56 PJ/yr, respectively, and least in the south-east at 52.36, 17.99 and 4.98 PJ/yr, respectively. The theoretical, technical and economical energy potentials of forest residues are highest in the north-west, estimated at 260.18, 156.11 and 43.18 PJ/yr, respectively, and least in the south-east at 1.79, 1.08 and 0.30 PJ/yr, respectively. Although most areas were identified to be suitable for siting biomass plants across Nigeria, the most suitable areas are located in the Northern part of the country, and include; Niger, Zamfara, the Federal Capital Territory, Nassarawa, Kano, Kebbi, Kaduna and Borno state. The study supports the Nigerian bio-energy policy that proposes to effectively utilize the Nigeria's non-fuelwood as substitute to felling of tress. This is very important to strengthen its commitment at COP26, which is to conserve and restore its forest. Furthermore, this study will serve as a good reference for policymakers to make wellinformed decisions on tackling the energy insecurity in Nigeria.